2014
DOI: 10.1155/2014/376207
|View full text |Cite
|
Sign up to set email alerts
|

A Brachytherapy Plan Evaluation Tool for Interstitial Applications

Abstract: Radiobiological metrics such as tumor control probability (TCP) and normal tissue complication probability (NTCP) help in assessing the quality of brachytherapy plans. Application of such metrics in clinics as well as research is still inadequate. This study presents the implementation of two indigenously designed plan evaluation modules: Brachy_TCP and Brachy_NTCP. Evaluation tools were constructed to compute TCP and NTCP from dose volume histograms (DVHs) of any interstitial brachytherapy treatment plan. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The multi-resolution scheme thus eliminates such non-trivial parameter tuning when solving HDR-BT planning. In general, our approach is quite flexible and capable of handling various types of problem difficulties and planning aims, thus allowing other kinds of treatment criteria to be considered during optimization, e.g., hot-spot restriction [34], tumor control probability (TCP) [35], or normal tissue complication probability (NTCP) [35]. Such criteria are important to be used in combination with DV indices, because it has been shown that in certain cases typical DV indices alone are not enough to describe what makes a treatment plan really good [36].…”
Section: Discussionmentioning
confidence: 99%
“…The multi-resolution scheme thus eliminates such non-trivial parameter tuning when solving HDR-BT planning. In general, our approach is quite flexible and capable of handling various types of problem difficulties and planning aims, thus allowing other kinds of treatment criteria to be considered during optimization, e.g., hot-spot restriction [34], tumor control probability (TCP) [35], or normal tissue complication probability (NTCP) [35]. Such criteria are important to be used in combination with DV indices, because it has been shown that in certain cases typical DV indices alone are not enough to describe what makes a treatment plan really good [36].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was assumed that the time interval between the fractions was sufficient to allow the full repair of sub-lethal damage, therefore G was considered as 1. The values of ρ and α were assumed to be constant throughout the target volume (ρ = 10 7 cells/cc, and α = 0.35 Gy -1 ) in the present study, which was also assumed in previous studies in the literature [ 13 , 20 ]. The assumption of constant ρ throughout HR-CTV could not be expressed due to lack of MRI-based planning.…”
Section: Methodsmentioning
confidence: 99%